2020
DOI: 10.1186/s12876-020-01390-0
|View full text |Cite
|
Sign up to set email alerts
|

An updated overview of spectrum of gluten-related disorders: clinical and diagnostic aspects

Abstract: The incidence of gluten-related disorders (GRDs) continues to increase and its global prevalence is estimated at approximately 5% of the population. Celiac disease (CD), dermatitis herpetiformis (DH), gluten ataxia (GA), wheat allergy (WA), and non-celiac gluten sensitivity (NCGS) are the five major GRDs that present with a wide range of clinical manifestations. The diagnosis of GRDs can be challenging because the typical and atypical clinical manifestations of the GRDs overlap. In this review, the current def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 153 publications
0
60
0
5
Order By: Relevance
“… 93 In fact, anti-tTG antibodies, made in response to gluten consumption, interact with the epidermal transglutaminase (ETG) enzyme and cause DH symptoms. 59 Allardyce and Shearman 94 in their study reported that cellular immune reactivity to the α-gliadin fraction was also observed in DH patients. Moreover, Huff et al 95 reported high levels of alpha-gliadin-specific antibodies in patients with DH ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“… 93 In fact, anti-tTG antibodies, made in response to gluten consumption, interact with the epidermal transglutaminase (ETG) enzyme and cause DH symptoms. 59 Allardyce and Shearman 94 in their study reported that cellular immune reactivity to the α-gliadin fraction was also observed in DH patients. Moreover, Huff et al 95 reported high levels of alpha-gliadin-specific antibodies in patients with DH ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 96%
“…Studies reported that CD has a prevalence of approximately 1–3% in the general population worldwide especially in Western societies. 58 , 59 CD is a gluten-induced immune-mediated inflammatory disorder of the small intestine caused by an intolerance to dietary gluten. CD is limited to genetically predisposed individuals who carry HLA-DQ2.5, HLA-DQ8, HLA-DQ2.2 and/or rarely HLA-DQ7 haplotypes located on the short arm of chromosome 6.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations